Network maintenance and troubleshooting guide - Allen, Neal. (Everett, WA : Fluke, 2002)
The 100% practical, real-world guide to anticipating, finding, and solving network problems$1 (Bfast! Real-life networks don$1 (Bt always behave (3z(Bby the book.(3y (BTroubleshooting them requires practical intuition that normally comes only with experience. In this book, Fluke Networks$1 (BNeal Allen brings together all that hard-won, hands-on insight: everything you need to discover what$1 (Bs really happening in your network, so you can anticipate and fix problems before users even notice them. Writing for network technicians and administrators at all levels, Allen presents an approach to troubleshooting that has been proven in networks of all kinds, no matter how complex. He introduces indispensable triage and troubleshooting techniques for everything from copper and fiber cabling to IPv6, and presents unparalleled guidance on identifying and resolving problems at the MAC Layer. He illustrates his advice with diagrams, tables, and screen captures from Fluke Networks$1 (Bmarket-leading instruments. Throughout this book, Allen also offers practical summaries of each of today$1 (Bs core networking technologies, making it an ideal complement to any network certification study guide.s
Preventing Problems. -- Solving Problems. -- Forming a Strategy. -- Appendix A: Errors. -- Appendix B: Operation. -- Appendix C: Troubleshooting. -- Appendix D: TCP/IP. -- Appendix E: IPX (Novell). -- Appendix F: Cable Testing. -- Appendix G: Switches. -- Appendix H: Glossary.
Includes index.
1
Keywords: Local area networks (Computer networks) -- Management; Local area networks (Computer networks) -- Maintenance and repair